As tramas da renda de bilro: transformações na produção artesanal no município de Raposa – MA - SERRÃO, Ádilla Danúbia Marvão Nascimento (2019)
This paper analyzes the transformations that occurred in the artisanal production of bobbin lace in the city of Raposa, Maranhão, considering the factors internal to the workspaces of the artisans, the interference of external agents and the repercussions of these actions on the lives of women. artisans. The increase in tourism and the intervention of exogenous institutions have contributed to changes not only in the characteristics of the pieces themselves but also in the production relations of women who are dedicated to making different artifacts with the bobbin lace technique. Using the theoretical framework of Elinor Ostrom's institutional analysis, we reflect on the implications of the action of exogenous institutions for artisanal production, seeking to grasp the interactions of the different agents in particularly configured action arenas. From fieldwork through direct and participant observation we seek to account for changes in production (volume, designs and price), circulation (growth of intermediaries, fairs, markets and stores) and consumption (taste seizure Raposense artisans) of this traditional handicraft and also the understanding of the role that each exogenous agent played in these transformations.